A FOLIA DE SÃO TOMÉ COMO TRAÇO ÉTNICO DA CULTURA AFRO-BRASILEIRA EM ÓBIDOS/PA - Tavares, Leandro de Castro (2018)
This Dissertation is linked to the Post-Graduation Program in History (Master's), from the State University of the Center-West (UNICENTRO), in the Line of Research Spaces of Practices and Power Relationships. It is inserted in the area of History and Regions and aims to identify and analyze the practice of Folia de São Tomé in Arapucu as an ethnic trait of Afro-Brazilian culture in the Municipality of Óbidos / PA, since the beginning of its practice in 1947. The research was carried out under the theoretical assumptions of Cultural History and, methodologically, is characterized as field, Oral History and documentary type. The research site is the Arapucu community, located in the municipality of Óbidos, an Amazonian mesoregion in the western part of the State of Pará. The methodological procedures used for data production were: bibliographic survey, semi-structured interview with Folia de São Tomé revelers and research documentary in local notaries. It is intriguing to think of valuing the practices of traditional peoples and their experiences, as this may be a determining factor for the construction of a positive identity. Thus, it is emphasized in the course of this research that the folklore practiced in the Arapucu community is seen as an Afro-Brazilian cultural practice, because all the existing folias in the municipality arose in remaining areas of quilombos, as well as the use, mainly, of instruments of African origin. Thus, the Folia de São Tomé is an ethnic trait of Afro-Brazilian culture in the Arapucu community. Taking into account also, that because there is the use of a Catholic Saint, there is a syncretic relation in this religious practice.